2013
DOI: 10.4236/jmp.2013.41003
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Signal and Data Analysis of Rock Media with Vertical Anisotropy

Abstract: This paper is concerned with anisotropic effects on seismic data and signal analysis for transversely isotropic rock media with vertical anisotropy. It is understood that these effects are significant in many practical applications, e.g. earthquake forecasting, materials exploration inside the Earth's crust, as well as various practical works in oil industry. Under the framework of the most accepted anisotropic media model (i.e. VTI media, transverse isotropy with a vertical axis symmetry), with applications o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Now, consider an incident P-wave from VTI to TTI medium with an incident angle (θ). For the TTI medium, Bond transformation can be used to convert its tilt-angle structure to the same tensor form of the VTI structure [24][25][26][27][28][29][30][31][32][33][34]; Kelvin-Christoffel equation can be solved for the reflected and refracted coefficients;…”
Section: The Interface Between Vti and Ttimentioning
confidence: 99%
See 1 more Smart Citation
“…Now, consider an incident P-wave from VTI to TTI medium with an incident angle (θ). For the TTI medium, Bond transformation can be used to convert its tilt-angle structure to the same tensor form of the VTI structure [24][25][26][27][28][29][30][31][32][33][34]; Kelvin-Christoffel equation can be solved for the reflected and refracted coefficients;…”
Section: The Interface Between Vti and Ttimentioning
confidence: 99%
“…While an interface between likewise-media has a relatively simple geometric structure [24][25][26][27][28][29][30][31][32][33][34], the interface between unlike-media can be much more complicated [35].…”
Section: Introductionmentioning
confidence: 99%
“…Ostrander [17] showed that AVO anomalies can indicate areas of Poisson's ratio change and are direct hydrocarbon indicators. However, anisotropy has potentially significant effects on AVO application and time-depth conversion of seismic data [18,19]. It is well known that elastic anisotropy is so common in Earth's interior that it is virtually impossible to avoid it in geophysical studies.…”
Section: Reflection/refraction Between Two Anisotropy Rock Slabsmentioning
confidence: 99%
“…Reflection and refraction of acoustic waves between adjacent rocks have profound implications in geophysics, e.g., in earthquake seismology, seismic image and analysis, and underwater acoustics [5][6][7][8][9][10][11]. The physical properties of the transversely isotropic media with a vertical axis of symmetry (VTI media), as shown in Figure 1(a), can be described by an elastic stiffness tensor [2,7,[12][13][14][15][16]…”
Section: Introductionmentioning
confidence: 99%